Continuous adsorption of lead ions in a column packed with palm shell activated carbon - Issabayeva, G.; Aroua, M.K.; Sulaiman, N.M. (Journal of Hazardous Materials, 2008)
The continuous adsorption of lead ions from aqueous solution on commercial, granular, unpretreated palm shell activated carbon (PSAC) was studied. Effect of pH, flow rates and presence of complexing agents (malonic and boric acids) were examined. The breakthrough period was longer at pH 5 indicating higher adsorption capacity of lead ions at higher pH. Increase of the flow rate, expectedly, resulted in the faster saturation of the carbon bed. Presence of complexing agents did not improve adsorption uptake of lead ions. However, presence of malonic acid resulted in smoother pH stabilization of solution compared to single lead and lead with boric acid systems. The results on continuous adsorption of lead were applied to the model proposed by Wang et al. Y.-H. Wang, S.-H. Lin, R.-S. Juang, Removal of heavy metals ions from aqueous solutions using various low-cost adsorbents, J. Hazard. Mater. B 102 (2003) 291-302. The agreement between experimental and modelled breakthrough curves was satisfactory at both pHs.